Infinitivo y sujeto en portugués y español : Un estudio empírico de los infinitivos adverbiales con sujeto explícito. - Vanderschueren, Clara (Beihefte zur Zeitschrift für romanische Philologie., 2013)
This volume sheds light on one of the most emblematic constructions in Ibero-Romance: adverbial infinitives with specified subjects, as in al entrar Juan (Sp), para eles verem o resultado (Ptg). From a cognitive-functional perspective and on the basis of elaborate empirical (corpus and psycholinguistic) analyses, the author examines which linguistic factors determine the use of the Portuguese inflected infinitive and of infinitives with overt nominative subjects in Spanish and Portuguese.